Allogeneic hematopoietic stem cell transplantation in aplastic anemia: current indications and transplant strategies. (May 2021) - Iftikhar, Raheel; Chaudhry, Qamar un Nisa; Anwer, Faiz; Neupane, Karun; Rafae, Abdul; Mahmood, Syed Kamran; Ghafoor, Tariq; Shahbaz, Nighat; Khan, Mehreen Ali; Khattak, Tariq Azam; Shamshad, Ghassan Umair; Rehman, Jahanzeb; et al.
Abstract: Treatment options for newly diagnosed aplastic anemia (AA) patient includes upfront allogeneic hematopoietic stem cell transplant (HSCT) or immunosuppressive therapy (IST). With recent advances in supportive care, conditioning regimens and post-transplant immunosuppression the overall survival for HSCT approaches 70–90%. Transplant eligibility needs to be assessed considering age, comorbidities, donor availability and probability of response to immunosuppressive therapy (IST). Upfront HSCT should be offered to children and young adults with matched related donor (MRD). Upfront HSCT may also be offered to children and young adults with rapidly available matched unrelated donor (MUD) who require urgent HSCT. Bone marrow (BM) graft source and cyclosporine (CsA) plus methotrexate (MTX) as graft versus host disease (GVHD) prophylaxis are preferable when using anti-thymocyte globulin (ATG) based conditioning regimens. Alemtuzumab is an acceptable alternative to ATG and is used with CsA alone and with either BM or peripheral blood stem cells (PBSC). Cyclophosphamide (CY) plus ATG conditioning is preferable for patients receiving MRD transplant, while Fludarabine (Flu) based conditioning is reserved for older adults, those with risk factors of graft failure and those receiving MUD HSCT. For haploidentical transplant, use of low dose radiotherapy and post-transplant cyclophosphamide has resulted in a marked reduction in graft failure and GVHD. Highlights: Transplant outcomes for aplastic anemia continues to improve with time, overall survival after MUD and Haploidentical transplant is now approaching MRD HSCT. Bone marrow graft source and cyclosporine plus methotrexate GVHD prophylaxis are preferable. Cyclophosphamide plus ATG conditioning is preferable for younger patients receiving MRD transplant, while Fludarabine based conditioning is reserved for older adults, with risk factors for graft failure and those receiving MUD HSCT.